2014
DOI: 10.4070/kcj.2014.44.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Previous Statin Therapy on Cholesterol-Lowering Effect of Ezetimibe

Abstract: Background and ObjectivesThe inhibition of cholesterol absorption by ezetimibe increases cholesterol synthesis. The effect of inhibition of cholesterol synthesis on cholesterol absorption is controversial. The influence of these interactions on cholesterol levels is unknown. We investigated on the extent to which cholesterol levels were affected by the reaction of one pathway to the inhibition of the other pathway.Subjects and MethodsThis case-controlled study enrolled 198 patients who needed cholesterol-lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We first reported that unexpectedly, statins dose-dependently significantly reduced adiponectin levels and insulin sensitivity and increased insulin and HbA1c levels despite improvement of endothelium-dependent dilation in hypercholesterolemic patients [7][8][9]16]. By contrast, ezetimibe improved liver steatosis and insulin sensitivity in animal studies [10,11] and significantly improved hepatic steatosis [12] and reduced visceral fat with beneficial effects on adiponectin and insulin resistance in patients with metabolic syndrome [13] and diabetes and insulin resistance [23] although it reduced LDL cholesterol levels further on statins [24].…”
Section: Discussionmentioning
confidence: 91%
“…We first reported that unexpectedly, statins dose-dependently significantly reduced adiponectin levels and insulin sensitivity and increased insulin and HbA1c levels despite improvement of endothelium-dependent dilation in hypercholesterolemic patients [7][8][9]16]. By contrast, ezetimibe improved liver steatosis and insulin sensitivity in animal studies [10,11] and significantly improved hepatic steatosis [12] and reduced visceral fat with beneficial effects on adiponectin and insulin resistance in patients with metabolic syndrome [13] and diabetes and insulin resistance [23] although it reduced LDL cholesterol levels further on statins [24].…”
Section: Discussionmentioning
confidence: 91%
“…Although data regarding cardiovascular protection of lipid-lowering therapy in FH is insufficient in Asian countries, a retrospective study in Japan found that CAD onset was delayed in FH patients after the widespread use of statins 46) . In Korea, ezetimibe is known to reduce LDL-C levels by 10% -19% 47,48) and is widely used in FH patients. According to data from the KSLA-supported study, statin -ezetimibe combination is used in about half of all registered patients (unpublished data).…”
Section: Effect Of Treatmentmentioning
confidence: 99%